Analysis Of The Efficiency Of Using Brushless DC Motors On Load And Speed On Electric Motorcycles - Erpita Samosir; Dicky Lesmana; Beni Satria (Sean Institute, 2025)
This study examines the efficiency of electric power in BLDC motors as electric motorcycle drivers with various load and speed experiments. Electric motorcycles are one of the vehicles that are in great demand by the public. BLDC motors are the main drivers of electric motorcycles where motor capacity planning includes motor power and torque which greatly affect the acceleration and speed of the motorcycle. Motor capacity planning is obtained by calculating the total weight, the location of the motor's center of gravity, the desired acceleration, tire rolling resistance to asphalt, air resistance and road slope angle. From the calculations and analyses that have been carried out, the required motor power is 2.5 kW. Testing the motor's ability to carry loads is carried out by providing variations in passenger and goods loads of 58 kg, 98 kg and 135 kg, and driven with a target speed of 10 km / h, 20 km / h and 30 km / h.